2013
DOI: 10.4236/aim.2013.31010
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Antimicrobial Lauric Arginate against <i>Listeria monocytogenes</i> on Stainless Steel Coupons

Abstract: Commercially processed foods become contaminated with Listeria monocytogenes in post-processing environments where favorable conditions help the bacteria thrive. The US Food and Drug Administration has approved Lauric arginate (LAE) as generally recognized as safe (GRAS) for certain food applications. This study evaluated the efficacy of Mirenat-N (LAE dissolved in food-grade propylene glycol) against L. monocytogenes on food contact surfaces. A three-strain cocktail of L. monocytogenes was used to inoculate 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…Additionally, survival of L. monocytogenes can be decreased by introducing antimicrobial compounds such as Lauric Arginate into stainless steel ( Saini et al . ), or by coating a stainless steel surface with an antimicrobial film, for example, TiN/Ag (Skovager et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, survival of L. monocytogenes can be decreased by introducing antimicrobial compounds such as Lauric Arginate into stainless steel ( Saini et al . ), or by coating a stainless steel surface with an antimicrobial film, for example, TiN/Ag (Skovager et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Listeria monocytogenes is a pathogenic bacterium, with human disease and infection linked to dairy products, seafood, ready-to-eat meat and raw and undercooked meats. Listeriosis, encompassing bacterial meningitis, sepsis, endocarditis, neonatal abortion and stillbirth in humans (Schlech et al 1983), usually presents in those who are already immunosuppressed, pregnant, old or young (Scholing et al 2007;Barocci et al 2015). During the late 1990s there was a large outbreak of listeriosis linked primarily to consumption of pât e (McLauchlin et al 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also very relevant and important to study whether inactive or injured bacterial cells can be differentiated from active and live bacterial cells using HSI (Anderson, Reynolds, Ringelberg, Edwards, & Floey, 2008). Lauric arginate (LAE) is a generally recognized as safe (GRAS) food-grade antimicrobial exhibiting activity against a wide range of pathogens (Saini, Miguel, Marsden, Getty, & Fung, 2013). The LAE has been studied for its use in food as an antimicrobial treatment and as a sanitizer for food contact surfaces (Becerril, Manso, Nerin, & Gómez-Lus, 2013;Saini, 2012).…”
mentioning
confidence: 99%
“…These features make LAE a promising antimicrobial preservative to control foodborne pathogens in food systems. Itinhibits a broad spectrum of foodborne pathogens (Ma, Davidson, & Zhong, 2013;Ma, Zhang, & Zhong, 2016;Porto-Fett et al, 2010) and, to date, LAE has been reported in many studies to be a highly efficient antimicrobial agent (Higueras, López-Carballo, Hernández-Muñoz, Gavara, & Rollini, 2013;Noll, Prichard, Khaykin, Sinko, & Chikindas, 2012;Saini, Barrios, Marsden, Getty, & Fung, 2013). In a recent study in our laboratories, the minimum inhibitory concentration (MIC) of LAE for inhibiting Listeria monocytogenes Scott A was found to be 11.8ppm in tryptic soy broth (TSB), while the MIC for Escherichia coli O157:H7 ATCC 43895 or Salmonella Enteritidis was 23.5 ppm (Ma et al, 2013).…”
Section: Introductionmentioning
confidence: 99%